(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The methanol extracts of bark and leaves of Chukrasia tabularis and their organic and aqueous soluble materials were subjected to screenings for antioxidant, cytotoxic, thrombolytic, membrane stabilizing, antimicrobial, analgesic and antidiarrhoel activities. In the DPPH free radical scavenging assay, the methanolic extract of bark of C. tabularis and the aqueous soluble fraction of methanol extract of leaves of C. tabularis revealed the highest free radical scavenging activity with IC50 values of 2.95 ?g/ml and 5.31 ?g/ml, respectively. The pet ether soluble fraction of methanolic extract of leaves and bark of C. tabularis displayed the highest cytotoxic potential having LC50 values 0.0167 ?g/ml and 3.89 ?g/ml, as compared to standard vincristine sulphate (LC50 value of 0.45 ?g/ml). During thrombolytic assay, the aqueous soluble fraction of leaves and carbon tetrachloride soluble fraction of bark of C. tabularis showed 34.04% and 56.37% clot lysis, respectively. In the membrane stabilizing assay, the carbontetrachloride and aqueous soluble materials of methanol extract of leaf inhibited 21.03% and 49.68% hypotonic solution- and heat-induced haemolysis of RBC, respectively. The crude extract of leaves of C. tabularis exhibited mild antibacterial activity, while that of leaves and bark revealed significant central analgesic activity at 400 mg/kg body weight. The crude extracts demonstrated significant peripheral analgesic activity at 200- and 400- mg/kg body weight. On the other hand, the crude extract of leaves of C. tabularis revealed significant antidiarrhoel activity. Bangladesh Pharmaceutical Journal 18(2): 126-131, 2015